Source-resolved PAHs links with microbial diversity and community structure in a multi-stressed coastal system, Saronikos Gulf, Greece (Eastern Mediterranean Sea) - Ester Skylaki; Alexandra Zachariadou; Savvas Genitsaris; Constantine Parinos; Konstantinos Proios; Ioannis Hatzianestis; Dimitris Velaoras; Aikaterina Rektsini; Maria Moustaka-Gouni; Alexandra Gogou (Marine Pollution Bulletin, 2026)

Influence of Hydrodynamic Regime on Living Coccolithophores in the Cretan Sea and South Cretan Area (Eastern Mediterranean) - Margarita D. Dimiza; Panagiota Syriopoulou; Elisavet Skampa; Constantine Parinos; Dimitris Velaoras; Pascal Conan; Mireille Pujo-Pay; Angela Maria Oviedo; Xavier Durrieu de Madron; Alexandra Gogou; Maria V. Triantaphyllou (Journal of Marine Science and Engineering, 2026)
Coccolithophores are important components of marine phytoplankton and are found to be useful indicators of the environmental conditions of the upper water column. In this study, we investigate coccolithophore abundance and composition in the Cretan Sea and South Cretan area (Eastern Mediterranean), and their relation to prevailing hydrodynamic conditions during late February/early March 2019. Results showed that total coccolithophore abundance ranged from 26.3 × 102 to 258.8 × 102 coccospheres L−1, averaging at 135.8 × 102 coccospheres L−1. Among the 45 identified species, the opportunistic Emiliania huxleyi was the most dominant, representing 89% of the coccolithophore assemblage. In the Cretan Sea, this species showed relatively homogeneous abundances throughout the upper 100 m depth of the water column; however, towards the Rhodes Cyclone, where a weak stratification had started, and the mixed layer was relatively shallow, higher abundances were found at depths shallower than 50 m. Syracosphaera molischii co-occurred with Emiliania huxleyi, whereas Rhabdosphaera clavigera, Syracosphaera pulchra, and Syracosphaera mediterranea were also present but in lower abundances, reflecting the influence of warm, salty Levantine Surface Water. Based on the morphological analysis, Emiliania huxleyi was mostly represented by heavily calcified forms consistent with winter-spring patterns in the Aegean Sea. The observation of signs of dissolution with high relative abundances of etched/corroded coccospheres indicates the sensitivity of Emiliania huxleyi to the prevailing circulation pattern during the 2019 mixing event within the Rhodes gyre.

Evidence of thermohaline staircase in the Cretan Sea (Eastern Mediterranean Sea) - Dimitris Velaoras; Sotiris Kioroglou; Evi Bourma; Dionysios Ballas; Vassilis Zervakis (Frontiers in Marine Science, 2025)
This work presents evidence of double diffusive convection (DDC) in the form of salt fingers (SF) forming a thermohaline staircase in the Cretan Sea (South Aegean Sea). The phenomenon was identified at the eastern edge of the Cretan Sea in March 2023 but had vanished by September 2023. To estimate vertical diffusivities and fluxes, four DDC models were applied to the hydrographic data. The vulnerability of the staircase appears to be related to weak, downward, salt finger–induced density fluxes, possibly caused by tilting of the salt fingers due to prevailing strong horizontal shears. Two of the four model implementations showed closer agreement with predictions from a previous staircase study in the area. Analysis of the density ratio and Turner angle from individual cruises demonstrated the widespread susceptibility of the Cretan Sea water column to such phenomena. Specifically, cruise data from 2016 to 2023, covering the layer between the intermediate salinity maximum (Levantine Intermediate Water) and the deep salinity minimum (Transitional Mediterranean Water), showed that 71%–85% of Turner angle values lie in the salt fingering zone. Thermohaline staircases in the Cretan Sea play a significant role in shaping the physical and biochemical processes of the basin by transporting salt and density toward deeper layers while uplifting nutrients. Although small scale, the phenomenon can significantly influence the evolution of the water column and large-scale climatic processes, such as vertical heat and salt transport and overturning circulation in deep basins.

A 1-Year Sediment Trap Study on the Downward Flux of Polycyclic Aromatic Hydrocarbons by Settling Particulate Matter in Deep Basins of the Aegean and Ionian Seas, Northeastern Mediterranean - Ester Skylaki; Constantine Parinos; Maria Tsagkaraki; Ioannis Hatzianestis; Anastasia Christidi; Elisavet Skampa; Ioanna Nikolopoulou; Georgia Kambouri; Ioanna Stavrakaki; Dimitris Velaoras; Giorgos Kouvarakis; Maria V. Triantaphyllou; et al. (Journal of Marine Science and Engineering, 2024)
This study investigates the composition, abundance, and vertical export of polycyclic aromatic hydrocarbons (PAHs) across three deep basins of the northeastern Mediterranean Sea (NEMS) over one year. Sinking particles were collected using sediment traps, and PAH analysis was conducted via gas chromatography-mass spectrometry. PAH fluxes varied significantly, peaking in the north Aegean Sea due to mesotrophic conditions, nutrient-rich riverine and Black Sea water inflows, and maritime anthropogenic inputs. The fluxes were highest in winter and lowest in fall. In the Cretan Sea, petrogenic sources (~70%) dominated, driven by currents, with fluxes highest in spring and lowest in winter. The Ionian Sea exhibited lower fluxes, peaking in summer and decreasing in fall. Atmospheric deposition seems to be the main transport pathway of pyrolytic PAHs in this site, while its high-water column depth (4300 m) compared to the other sites presumably enables extended degradation of organic constituents during particle settling. The positive matrix factorization (PMF) and principal component analysis (PCA) results reveal complementary insights into PAH sources and transport mechanisms. PMF analysis identified combustion (61%) and petrogenic (22%) sources, while PCA highlighted biogenic fluxes (57.7%) and atmospheric deposition. Seasonal productivity, riverine inputs, and water circulation shaped PAH variability, linking combustion-related PAHs to atmospheric soot and petrogenic PAHs to organic-rich particles.

A first scoring approach for evaluating the European Ocean Observing Community - Abed El Rahman Hassoun; Toste Tanhua; Emma Heslop; Inga Lips; Marta Álvarez; George Petihakis; Maribel I. García-Ibáñez; Dimitris Velaoras; Michele Giani; Hermann W. Bange; Christian Lønborg; Johannes Karstensen (Frontiers in Marine Science, 2024)
The European Ocean Observing Community (EOOC) integrates inputs from diverse entities dedicated to comprehensively monitoring and forecasting oceanic phenomena in European Seas. With increasing climate and anthropogenic pressures, the urgency of ensuring the EOOC’s preparedness to observe Essential Ocean Variables (EOVs) is evident. This paper advocates for the adoption of a scoring approach designed to evaluate the readiness of the EOOC in observing and forecasting key ocean phenomena. The proposed scoring methodology can be applied at both European and potentially regional and/or national levels, and emerges as a transformative tool for scrutinizing the EOOC’s capability to predict and monitor key ocean phenomena. Our findings, based on the application of the scoring approach, suggest that while the community demonstrates commendable readiness levels for certain oceanic phenomena, 83% remain in developing stages, oscillating between “Idea” and “Trial” readiness levels. A closer examination exposes critical shortages predominantly in the coordination and observational facets (Process), and data management and information products (Output). The implications of these identified gaps reach far beyond academic realms, profoundly affecting diverse sectors and societal resilience (e.g., energy sector). The suggested scoring approach serves as a clear call for strategic investments and heightened support for the European observing community. By adopting a regular and systematic scoring methodology, we not only measure progress at present but also pave the way for a resilient and future-ready EOOC.

A consensus-based, revised and comprehensive catalogue for Mediterranean water masses acronyms - KATRIN SCHROEDER; SANA BEN ISMAIL; MANUEL BENSI; ANTHONY BOSSE; JACOPO CHIGGIATO; GIUSEPPE CIVITARESE; FRANCESCO FALCIERI M; GIANNETTA FUSCO; MIROSLAV GAČIĆ; ISAAC GERTMAN; ELISABETH KUBIN; PAOLA MALANOTTE-RIZZOLI; et al. (Mediterranean Marine Science, 2024)
Addressing the need for clear communication in Mediterranean oceanography, this study presents a revised and comprehensive catalogue of water mass acronyms. Although there is no universal set of standard rules for assigning acronyms to water masses, as these can vary among different research groups, regions, or scientific communities, scientists generally aim for clarity and consistency when naming and abbreviating water masses to facilitate communication within the scientific community. The team of experts, guided by the CIESM (the Mediterranean Science Commission) C2 Committee on the Physics and Climate of the Ocean, reviewed existing literature and established new acronyms and naming guidelines. This standardized system, emphasizing clarity and consistency, replaces the current variable practices employed by different research groups.

Holocene Climatic Optimum centennial-scale paleoceanography in the NE Aegean (Mediterranean Sea) - Maria V. Triantaphyllou; Alexandra Gogou; Margarita D. Dimiza; Sofia Kostopoulou; Constantine Parinos; Grigoris Roussakis; Maria Geraga; Ioanna Bouloubassi; Dominik Fleitmann; Vassilis Zervakis; Dimitris Velaoras; Antonia Diamantopoulou; et al. (Geo-Marine Letters, 2016)